PERLINDUNGAN KONSUMEN AKIBAT KERUGIAN YANG DITIMBULKAN PENERBITAN BROSUR PERUMAHAN YANG DILAKUKAN PENGEMBANG - I KADEK ADI SURYA (GANEC SWARA, 2023)
The definition of promotion according to Article 1 number 6 of Law Number 8 of 1999 concerning Consumer Protection is the activity of introducing or disseminating information on goods and/or services to attract consumers' buying interest in goods and/or services that will be and are being traded. As we all know, brochures are one of the promotional media that are often used by businesses as a means to market a product or service. Usually brochures contain pictures and product descriptions that businesses want to market and usually product marketing through brochures is carried out in crowded places such as malls, streets or places that are deliberately provided such as exhibitions. Advertising through the brochure is also to attract consumer buying interest in the products being traded, in this case housing. However, behind the promotional activities using this brochure, there are many negative things done by the developer (developer), it is not uncommon for the public's trust to be misused by the developer. In making housing offers, it is not uncommon for the information provided by the developer to be too much so that it makes consumers very interested or maybe even confusing for the consumers themselves, the purpose of this research is to provide legal protection to consumers who are harmed by brochures promoted by developers that are not in accordance with the truth stated. If there is, then with the existing problems, this research uses normative legal research, which is a process to find a rule of law, legal principles, or legal doctrines to answer the legal issues at hand.